Folklor non-verbal dalam praktik multikultural di desa Jedong: Kajian sensorik terhadap bau dupa dan sesajen - afida, mila nur (Maliki Interdisciplinary Journal, 2025)
This article examines non-verbal folklore in the ritual practices of a multicultural community in Jedong Village, Wagir District, Malang Regency. The research focuses on sensory experiences, particularly the smell of incense and offerings such as flowers and food placed in public spaces. Using a qualitative approach and ethnographic methods, this article shows that sensory elements in rituals not only function as spiritual symbols but also as a medium for social interaction, collective memory, and cultural identity amid religious diversity (Hinduism, Islam, and Christianity). These findings reinforce the position of sensory folklore as part of non-verbal folklore studies and open up new avenues for understanding tolerance and inter-religious cultural life in rural East Java.